PENGARUH KONSEP DIRI DAN DISIPLIN TERHADAP EFEKTIVITAS KERJA GURU SMA NEGERI DI KABUPATEN FLORES TIMUR, NUSA TENGGARA TIMUR - Vinsensius Crispinus Lemba (Jurnal Manajemen Pendidikan, 2012)
The objective of this research is to obtain the influence of self concept and discipline on work effectiveness of the State Senior High School teachers in East Flores District. The research was conducted by using a survey method with path analysis technique in testing hypothesis. The sample size was 112 teachers, were selected randomly. The results of the research are as follows: first, there is a positive influence directly self concept on effectiveness work; second, there is a positive influence directly discipline on effectiveness work; third, there is a positive influence directly self concept on discipline. The findings lead to the recommendation for the State Senior High School teachers in East Flores District to increase their work effectiveness by increasing self concept and discipline. It is also recommended that principals must support the teachers’ efforts to increase self concept, discipline and work effectiveness.